‘My Cloudy Melancholy’: Productions of Whiteness in Titus Andronicus (1594) - Ziegler, Molly (Early Theatre, 2025)
This paper examines the significance of Aaron’s melancholy toward the production of whiteness in Shakespeare’s Titus Andronicus. While the word ‘melancholy’ only appears once, Aaron’s self-confessed temperament becomes a key tool in the play’s efforts to define race along moral and physical lines. This paper explores how Aaron becomes a resource in securing the play’s representation of a white, Roman legacy, and how the commodification of Black bodies resonates with early modern constructions of race and the formation of a racially delineated hierarchical system.